De Haas-van Alphen effect and superconductivity - Gor`kov, L.P.; Landau, L.D. (Физика низких температур, 1999)
The problem of the robust de Haas-van Alphen oscillations seen experimentally in mixed superconducting state is discussed. The new threshold mechanism is suggested to explain persistence of the quantum oscillations deep in the superconducting state.